THE GUT-BRAIN AXIS IN NEURODEGENERATIVE DISEASES AND MOOD DISORDERS: MECHANISMS AND SCIENTIFIC EVIDENCE - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
The gut–brain axis (GBA) is a complex, bidirectional communication system between the central and enteric nervous systems and the gut microbiota. Increasing evidence points to its key role in the pathogenesis of neurodegenerative diseases and mood disorders, such as Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, depression, and anxiety disorders.Communication within the GBA occurs through neural, immune, and endocrine pathways, with microbial metabolites-including short-chain fatty acids, tryptophan derivatives, and cytokines-playing a crucial role in neuroinflammatory and neurodegenerative processes. Gut dysbiosis, increased intestinal barrier permeability, and vagus nerve dysfunction link intestinal abnormalities with brain dysfunction.Preclinical and clinical studies suggest that modulation of the microbiota-through diet, probiotics, prebiotics, or fecal microbiota transplantation-may have therapeutic potential in neuropsychiatric and neurodegenerative diseases. However, individual variability, methodological limitations, and ethical considerations hinder the practical implementation of these strategies in clinical practice.Understanding the functioning of the gut–brain axis may open new avenues for the prevention and treatment of neurological and psychiatric disorders through targeted interventions on the gut microbiota.